PULMONARY ARTERY PSEUDOANEYRYSM: A POST-COVID COMPLICATION - Shah, Sajida; Malik, Zainab; Bhinder, Khurram Khaliq; Shah, Mariam (Journal of Ayub Medical College Abbottabad, 2023)
We present a case report of a potentially lethal post-COVID complication. A 65-year-old male presented with shortness of breath and fever with chills. He had recently recovered from COVID pneumonia. Contrast enhanced CT scan chest gave the suspicion of pulmonary pseudoaneurysm. CT aortogram revealed a well-defined rounded mass in the right lung mainly occupying the lower lobe of right lung. Angiography through right common femoral vein was performed and it confirmed a huge pseudoaneurysm arising from the posteromedial branch of the right descending interlobar artery. As the artery was not found suitable for endovascular embolization, the patient was referred to thoracic surgeon.